Social change in medieval Iran 132-628 AH (750-1231 AD) : the perspectives of Persian historiography - Kamālī, Maryam (Amsterdam : Amsterdam University Press, 2023)
This study contributes to the history of social changes in Iran during the Abbasid Caliphate (AH 132-656, AD 750-1258) by foregrounding the perspective of Persian language historians - from Abu Ali Bal'ami (AH 363, AD 974), the first known Persian historian, to Atamelak Joveyni (AH 623-681, AD 1226-1283), the great historian of the Mongol Era. By applying the insights of Anthony Giddens and the theory of structuration to address the interactions of social agents and structures, this book provides a coherent narrative of social transformation in medieval Iran.
Preface -- Introduction -- Author's notes -- Part I. The formation of Iranian authority under the ʻAbbāsid Caliphate -- 1. The formation of the ʻAbbāsid Caliphate. -- 2. Establishment of the ʻAbbāsid Caliphate -- 3. Split in the ʻAbbāsid political structure -- Part II. The structure of Iranian dynasties. from dependence to independence -- 4. The rule of the Tāherids in the shadow of the ʻAbbāsid Caliphate -- 5. The structure of the Sāmānid government. Moving in the direction of cultural independence -- 6. The Saffārid Dynasty . A power outside the ʻAbbāsid structure -- 7. The ʻAlawites of Tabarestān, the first Shiʻite dynasty in Iran -- 8. The Buyid dynasty . A turning point in Iran's social change -- Part III. The rise of soltānates in the power structure -- 9. The formation of the Ghaznavid soltānate -- 10. The Saljuq dynasty . The first Islamic empire in Iran -- 11. The Khwārazmshāhi dynasty: Emerging from the Saljuq structure -- Conclusion -- Bibliography -- Index
"Amsterdam University Press"
Table of Contents Dedication Preface Introduction Author's Notes Part I The Formation of the Iranian Authority under the .Abb.sid Caliphate Introduction Chapter 1: The Formation of the .Abb.sid Caliphate: from Secret Da.va to the Rise of Siy.h-J.meg.n (the Black Garments) Bibliography Chapter 2: Establishment of the .Abb.sid Caliphate, Restructuring or Displacement of Agents Keywords: .Abb.sids, D..ies, Abu Moslem, Iranian Vazirs, Barmakids Bibliography Chapter 3: Split in the .Abb.sid Political Structure, A Prelude to the Independence of Khor.s.n Keywords: The .Abb.sids, Khor.s.n, Baghdad, Ma.mun, T.her Bibliography Part II The Structure of Iranian Dynasties: From Dependence to Independence Introduction Chapter 4: T.herid's Rule in the Shadow of .Abb.sid Caliphate Keywords: The T.herid dynasty, B.bak, M.ziy.r, Afshin Bibliography Chapter 5: The Structure of the S.m.nid Government, Moving in the Direction of Cultural Independence Keywords: The S.m.nid Dynasty, Iranian border guards and bureaucrats, Ism..ilis Bibliography Chapter 6: The Saff.rid Dynasty, a Power outside the .Abb.sid Structure Keywords: The Saff.rid dynasty, Ya.qub-e Leys, Sist.n, The Ayy.rs Chapter 7: .Alawites of Tabarest.n, the First Shi.ite Dynasty in Iran Keywords: The Buyid Dynasty, Deylamis, the Shi.ites, the Eqt.. Chapter 8: The Buyid Dynasty: A Turning Point in Iran's Social Change Bibliography Part III The Rise of Solt.nates in the Power Structure Chapter 9: The Formation of the Ghaznavid Solt.nate Chapter 10: The Saljuq Dynasty, the First Islamic Empire in Iran Chapter 11: The Khw.razmsh.hi Dynasty Emerging from the Saljuq Structure Bibliography Conclusion References
Includes bibliographical references and index
Description based on online record; title from PDF title page (Cambridge Core, viewed February 19, 2024).
eBooks on EBSCOhost
Keywords: Iran -- History -- 640-1256.; Iran -- Histoire -- 651-1256.; Early history: c. 500 to c. 1450/1500.; Social and cultural history; HISTORY / Middle East / Iran; HISTORY / Medieval; HISTORY / Social History; Iran; Historiography; Middle Eastern history; 640-1256; History, Art History, and Archaeology; HIS; Antiquity; ANTIQ; Islam; Medieval Studies; MEDIEVAL; Middle East; MID EAST; Social Change, Medieval Iran, Abbasid Caliphate, Persian Language Historiography; History